Determinants of Profitability in Manufacturing: A Comprehensive Analysis - Muhammad Muharror Fuadi; Nurma Gupita Dewi (TEMA, 2025)
Profitability is a description of a company's ability to make a profit. The urgency of researching corporate profitability lies in its critical role as a primary indicator of a company’s financial health, sustainability, and competitive advantage. The study used the dependent variable Profitability, while the independent variables were capital structure, leverage, and company size. The population used was all food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The data collection technique employed in the study was a combination of the documentation method and purposive sampling, which produced samples that met the research criteria. The research sample consisted of 18 companies with 54 observations. The data analysis technique in this study employed multiple linear regression analysis, previously tested against classical assumptions to obtain the Best Linear Unbiased Estimate (BLUE). The results of this study indicate that capital structure and leverage have a negative but statistically insignificant effect on profitability. In contrast, company size has a positive but statistically insignificant effect on profitability.